Potential for a booster dose of rotavirus vaccine to further reduce diarrhea mortality. Issue 51 (18th December 2017) - Burnett, Eleanor; Lopman, Ben A.; Parashar, Umesh D.
Abstract: Concern has grown that children vaccinated against rotavirus in developing countries may be vulnerable to rotavirus diarrhea in the second year of life due to waning immunity. Adding a booster dose of rotavirus vaccine at 9 or 12 months of age with measles vaccine has been suggested as a strategy to address this. We evaluated the hypothetical potential benefits of a booster dose on reduction of rotavirus mortality. The projected number of deaths averted were calculated using national level full series vaccination coverage, estimated national rotavirus deaths by week of age, and VE at <12 months of age and ≥12 months of age derived from the published literature. We assumed three functional forms of waning based on the VE estimates: stepwise, linear, and logarithmic. We modeled three potential boosting scenarios: (a) reduced VE waning in the second year of life by 50%, (b) reestablished second year of life VE to the levels in the first year of life, and (c) boosted first year VE by 50% of the difference between VE in the first and second years. To express uncertainty resulting from the parameters, each of the nine models were run 1000 times using a random sample of input values. Across all WHO regions, with the stepwise models we estimated a median of 9800 (95%CI: 9400, 10, 200), 19, 600 (95%CI: 18, 800, 20, 400), and 29, 400 (95%CI: 28, 200, 30, 700) additional rotavirus deaths averted in the reduced VE waning, reestablished VE, and boosted VE scenarios. These estimates were highly sensitive to the assumed functional form of waning with approximately 65–80% fewer deaths averted if immunity waned in a linear or logarithmic fashion compared to the stepwise model. While these projections will benefit from improved input data points, our results inform consideration of booster doses of rotavirus vaccine.